MICROALGAE BIOPOLYMERS: A REVIEW - Zatta, P. H. S.; Jacob-Furlan, B.; Mirabile, R. C.; Gonçalves, R. S. R.; da Silva, P. A. S.; Taher, D. M.; Lira, G. S.; Martins, L. S.; Ordonez, J. C. (Revista de Engenharia Térmica, 2023)
Algae are ubiquitous organisms whose capabilities have drawn much attention as of late in the bioengineering field due to their potential to enable a wide range of bioproducts. Microalgae are ideal organisms for the application of the biorefinery concept since they can be grown in wastewater and, at the same time, produce many products of commercial interest. These microorganisms are also known for their resilience to extreme environmental conditions and suitable cell growth rates. Beyond the known potential for biofuel production, these microorganisms can still produce other compounds, being lipids, pigments, vitamins, proteins, and polysaccharides, whose applications go from pharmaceutical to agricultural industries. Recently, the research focus has been directed to the biopolymer-producing ability of both micro- and macroalgae, as they can be rather varied and useful to many applications. However, this is still an ongoing research field, and new data are frequently added in the literature, notably on biomass processing, which can be done with the intent of use into dyes, bioplastics, paints, and even as biochar in solid fuel cells. Microalgae-based biopolymers can be used in a wide range of products, nevertheless, the resulting process efficiency and yields depend on the extraction process utilized, as well as on the microalgae species used and the culture conditions. Furthermore, the polymer extraction can be done directly with common solvents at atmospheric pressure or with other fluids, such as supercritical CO2 or subcritical solvents, and assisted by specific treatments, e.g., ultrasound and microwave. The residual biomass can still be used to produce other less valuable products, such as feedstock, and energy via combustion. In this sense, the present work aims to provide a state-of-the-art review on microalgae biopolymers. Issues related to the efficiency of current treatment methods, industrial applications, and environmental performance are presented and discussed. Besides, the perspectives in this area of knowledge are also a contribution of the present work, the extent to which scientific research is still under development.